2010
DOI: 10.15288/jsad.2010.71.506
|View full text |Cite
|
Sign up to set email alerts
|

Spouses of Older Adults With Late-Life Drinking Problems: Health, Family, and Social Functioning

Abstract: ABSTRACT. Objective: This study focuses on the health, family, and social functioning of spouses of late-life remitted and continuing problem drinkers, and on predictors of spouses' alcohol-related functioning and depressive symptoms. Method: Three groups of spouses were compared at baseline and a 10-year follow-up: (a) spouses (n = 73) of older adults who had no drinking problems at baseline or followup, (b) spouses (n = 25) of older adults who had drinking problems at baseline but not follow-up, and (c) spou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…They found similar results, with spouses of those with alcohol dependence having higher rates of depression, psychiatric morbidity and stress along with lower scores on physical and psychological well-being [3]. Moos et al conducted a study on older adults but found similar results, that is, spouses of those men who continued drinking had greater depression and poorer overall health when compared with spouses of men who never drank as well as those men who had stopped drinking several years back [10]. While the population of this study was different from ours, the results are still significant as this was a longitudinal study.…”
Section: Discussionmentioning
confidence: 88%
“…They found similar results, with spouses of those with alcohol dependence having higher rates of depression, psychiatric morbidity and stress along with lower scores on physical and psychological well-being [3]. Moos et al conducted a study on older adults but found similar results, that is, spouses of those men who continued drinking had greater depression and poorer overall health when compared with spouses of men who never drank as well as those men who had stopped drinking several years back [10]. While the population of this study was different from ours, the results are still significant as this was a longitudinal study.…”
Section: Discussionmentioning
confidence: 88%
“…Good reliability, stability, and convergent and predictive validity has been established for the HDL in this long-term study of depression (Holahan et al, 1999;Moos et al, 1998aMoos et al, , 1998b as well as in other long-term, naturalistic studies, such as those of health in middle and older age Moos et al, 2010;Moos et al, 2011) and individuals initially untreated for substance use disorders (Moos & Moos, 2002, 2005Timko et al, 2006Timko et al, , 2011.…”
Section: Methodsmentioning
confidence: 94%
“…Alternatively, adult children’s strain with parents may relate to parents’ own substance use. For example, strain may be in response to a parents’ problematic health behavior, and in turn may promote a reduction of this behavior in adult children (Glass, Prigerson, Kasl, & de Leon, 1995; Moos, Brennan, Schutte, & Moos, 2010). Strain with parents may inadvertently reduce children’s substance use if the parent and child performed the behavior together; strain may lower the chance of unhealthy contagion (Christakis & Fowler, 2013).…”
Section: Discussionmentioning
confidence: 99%